2018
DOI: 10.1016/j.appet.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gluten free diet adherence and depressive symptoms in adults with coeliac disease: A systematic review with meta-analysis

Abstract: Conflicts of interest: none Funding: none 2The relationship between gluten free diet adherence and depressive symptoms in adults with coeliac disease: A systematic review with meta-analysis ABSTRACT Purpose: Depressive symptoms are common in patients with coeliac disease (CD) and may represent a barrier to gluten free diet (GFD) adherence. The aims of this meta-analysis were: (1) to synthesise the evidence on the relationship between depression or depressive symptoms and degree of adherence to a GFD in patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 60 publications
3
23
1
2
Order By: Relevance
“…The still significant influences 15 of PBC and support (albeit reduced) suggest that these factors may be protective in the presence of 16 distress. These findings extend previous work (Sainsbury & Marques, 2018) by suggesting specific 17 means via which depression may impact the intention-behaviour gap.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The still significant influences 15 of PBC and support (albeit reduced) suggest that these factors may be protective in the presence of 16 distress. These findings extend previous work (Sainsbury & Marques, 2018) by suggesting specific 17 means via which depression may impact the intention-behaviour gap.…”
supporting
confidence: 86%
“…Understanding the modifiable determinants of poor adherence is essential for the 16 design of evidence-based strategies to improve dietary adherence and health. We and others have 17 shown that a range of patient factors including food label-reading skills, degree of symptomatology 18 to gluten exposure (Halmos et al, 2017), and depressive symptoms (Sainsbury & Marques, 2018), 19 are associated with, and likely to influence, both behaviour and dietary adherence, but ultimately 20 patient behaviour is the most important and modifiable determinant. One means to the 21 development of interventions is the use of health behaviour change theory (e.g., Craig et al, 2008).…”
mentioning
confidence: 98%
“…This is also corroborated by studies of people on gluten-free diets, where depression, anxiety, or disordered eating is associated with poorer adherence to a gluten-free diet among people with coeliac disease [14]. The relationship between depression and poor adherence in coeliac disease has been confirmed in a recent meta-analysis [15], however, these authors note that the direction of this relationship remains unclear, as poor adherence would be expected to negatively affect health (at a minimum, physical health) in this population. The possibility that poor mental health is an outcome (rather than a cause) of poor adherence is corroborated by studies of supervised, formal, lifestyle-modification programs.…”
Section: Mental Health and Its Link To Dietary Adherencementioning
confidence: 61%
“…Data on dietary adherence of a gluten-free diet in a coeliac disease population are variable, with rates ranging between 42% and 91%, depending on definition and method of assessment. 13 Studies from North America and Europe have associated dietary adherence with higher levels of education, younger age at diagnosis, 11,13,14 membership of coeliac disease advocacy groups, 10 quality of life and mental disorders 15,16 but sample sizes have been small and possibly not representative at a population level. However, examination of clinically relevant factors that may be targeted in patient management to improve adherence, such as food knowledge, quality of life and psychological distress, have remained unexplored in Australia and New Zealand, where there is high prevalence of coeliac disease and a stricter definition of a gluten-free diet compared to other countries.…”
Section: Introductionmentioning
confidence: 99%